Pengaruh Gel Binahong (Anredera cordifolia (Ten.) Steenis) terhadap Penyembuhan Luka Tikus Diabetes yang Diinduksi Aloksan (The Effect of Binahong (Anredera cordifolia (Ten.)Steenis) Gel on Wound Healing Process of Diabetic Rats Induced by Alloxan) - Shinta Cholifatu Rohma; Evi Umayah Ulfa; Diana Holidah (UPT Percetakan dan Penerbitan Universitas Jember, 2015)
Diabetes Mellitus (DM) is a chronic disease that can be indicated by the increase of blood glucose level. Diabetic ulcer is one of complication caused by DM. Binahong (Anredera cordifolia (Ten). Steenis) has a potential effect to heal the wound. The purpose of this study was to examined the effect of binahong gel on the wound healing process of diabetic rats induced by alloxan. The observation was done on the wound's histopathological preparation. The wound were made on diabetic rats, then the binahong gel at a dose of 100 mg and 200 mg were spread on to their wounds. The observation of qualitative descriptive parameters consisted of epithelial tissue, collagen, and new blood vessels formation. The results showed that binahong gel was able to accelerate the wound healing process of diabetic ulcer. Keywords: Anredera cordifolia, diabetic ulcer, wound healing, alloxan, histopathological profile